2014
DOI: 10.1007/s10549-014-3115-3
|View full text |Cite
|
Sign up to set email alerts
|

High risk of in-breast tumor recurrence after BRCA1/2-associated breast cancer

Abstract: The purpose of the study was to compare breast-conserving therapy (BCT) and mastectomy (M) in BRCA1/2 mutation carriers. Women with invasive breast cancer and a pathogenic mutation in BRCA1 or BRCA2 were included in the study (n = 162). Patients treated with BCT (n = 45) were compared with patients treated with M (n = 118). Endpoints were local recurrence as first recurrence (LR), overall survival (OS), breast cancer death, and distant recurrence. Cumulative incidence was calculated in the presence of competin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 25 publications
2
47
0
1
Order By: Relevance
“…This is somewhat uncommon timing compared to the literature. As previously discussed, the overall risk of locoregional recurrence for patients undergoing mastectomy is 5%‐10% over 10 years; however, for BRCA‐positive patients, this risk increases to 15% and 25% after 5 and 10 years, respectively . For the patient discussed in this report, the BRCA‐associated risk of locoregional recurrence is more difficult to assess.…”
Section: Review Of the Literature And Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This is somewhat uncommon timing compared to the literature. As previously discussed, the overall risk of locoregional recurrence for patients undergoing mastectomy is 5%‐10% over 10 years; however, for BRCA‐positive patients, this risk increases to 15% and 25% after 5 and 10 years, respectively . For the patient discussed in this report, the BRCA‐associated risk of locoregional recurrence is more difficult to assess.…”
Section: Review Of the Literature And Discussionmentioning
confidence: 74%
“…As previously discussed, the overall risk of locoregional recurrence for patients undergoing mastectomy is 5%-10% over 10 years; however, for BRCA-positive patients, this risk increases to 15% and 25% after 5 and 10 years, respectively. 13 For the patient discussed in this report, the BRCA-associated risk of locoregional recurrence is more difficult to assess. As previously noted, the patient underwent genetic testing and was determined to have a T37K variant, a missense mutation in the BRCA1 ring finger domain.…”
Section: Literature and Discussionmentioning
confidence: 98%
“…1.1e7.8) [59]. While all inbreast events were observed in the first 5 years in the Table 3 Rates of cause-specific and overall survival following breast conserving surgery and PORT in BRCA1 e BRCA2 carriers compared with controls.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, caution is urged when analyzing the results of retrospective studies on local control in early stage BRCA1/2 mutation-associated breast cancer patients. Table 1 shows that the majority of the reports did not find any significant difference in in-breast events between carriers and noncarriers [28,37,43,50,51,58,59]. In one of the few studies linking a significantly higher risk of local failure over time to the presence of a BRCA1/2 mutation, Haffty et al, using a multivariate step-wise Cox regression analysis adjusted for age, identified BRCA1/2 mutation status to be an independent predictor for IBTR with 49% tumour events observed in patients with a BRCA1/2 mutation vs 21% in the control group after 12-year follow-up (p ¼ 0.007) [40].…”
Section: Biological Backgroundmentioning
confidence: 99%
“…We have excluded this therapy option, as a strong riskreducing effect of chemoprevention for all age groups and mutation types is uncertain (Duffy andNixon 2002, King et al 2001). The risk of breast cancer recurrence or a contralateral breast cancer (i.e., a new tumor in the opposite breast of the original tumor) is significant for mutation carriers (Graeser et al 2009, Nilsson et al 2014. As the state space structure does not account for recurrences or contralateral breast cancer and these states would alter a carrier's mortality, our model is limited by the accuracy of the breast cancer mortality rate.…”
Section: Limitationsmentioning
confidence: 99%